Studying The Learning Effect In Visual Field Testing Using Automated Perimetry - يوسف حبيب; كردغلي نجوى; بري نسرين (Latakia University Journal -Medical Sciences Series, 2021)
Purpose: to study the influence of learning effect on the outcome of automated perimetry and to assess the factors associated with the learning effect. Materials and Methods: In this cross sectional study we studied 122 subjects who had not previously undertaken any form of perimetry. Each subject completed two testing sessions, each separated by half hour in the same day. The Octopus900 G program test included both eyes. The right eye was always tested before left eye. We divided the subjects into two groups ( healthy and glaucoma). The reliability parameters, test duration and visual field (VF) global indices (mean deviation [MD], mean sensitivity [MS] and Square root of Loss Variance [SLv] ) obtained from right eyes in the first and second test were compared to assess the learning effect. Change in these parameters between the first and second sessions was calculated, and the effect of gender, age and educational level on this change was evaluated. Results: The reliability parameters, test duration and VF global indices improved between the first and second sessions (P ≤ 0.001). The improvement was better in healthy group. The change in the parameters was greater in subjects over 50 years of age (P ≤ 0.01). No correlation was found between learning effect and gender and educational level. Conclusion: a significant learning effect was observed during VF testing with the Octopus900 G program. The learning effect was correlated with age.